The Vasoactive Role of Perivascular Adipose Tissue and the Sulfide Signaling Pathway in a Nonobese Model of Metabolic Syndrome - Cacanyiova, Sona; Golas, Samuel; Zemancikova, Anna; Majzúnová, Miroslava; Cebova, Martina; Malinska, Hana; Hüttl, Martina; Markova, Irena; Berényiová, Andrea (Biomolecules, 2021)
The aim of this study was to evaluate the mutual relationship among perivascular adipose tissue (PVAT) and endogenous and exogenous H2S in vasoactive responses of isolated arteries from adult normotensive (Wistar) rats and hypertriglyceridemic (HTG) rats, which are a nonobese model of metabolic syndrome. In HTG rats, mild hypertension was associated with glucose intolerance, dyslipidemia, increased amount of retroperitoneal fat, increased arterial contractility, and endothelial dysfunction associated with arterial wall injury, which was accompanied by decreased nitric oxide (NO)-synthase activity, increased expression of H2S producing enzyme, and an altered oxidative state. In HTG, endogenous H2S participated in the inhibition of endothelium-dependent vasorelaxation regardless of PVAT presence; on the other hand, aortas with preserved PVAT revealed a stronger anticontractile effect mediated at least partially by H2S. Although we observed a higher vasorelaxation induced by exogenous H2S donor in HTG rats than in Wistar rats, intact PVAT subtilized this effect. We demonstrate that, in HTG rats, endogenous H2S could manifest a dual effect depending on the type of triggered signaling pathway. H2S within the arterial wall contributes to endothelial dysfunction. On the other hand, PVAT of HTG is endowed with compensatory vasoactive mechanisms, which include stronger anti-contractile action of H2S. Nevertheless, the possible negative impact of PVAT during hypertriglyceridemia on the activity of exogenous H2S donors needs to be taken into consideration.
Keywords: Disease Models, Animal; Animals; Metabolic Syndrome; Hypertriglyceridemia; Rats, Wistar; tuková tkáň; mužské pohlaví; noradrenalin; Signal Transduction; superoxidy; oxidace-redukce; Vasoconstriction; Norepinephrine; synthasa oxidu dusnatého, typ III; cystathionin-gama-lyasa; modely nemocí na zvířatech; vazokonstrikce; superoxiddismutasa; aorta thoracica; Adipose Tissue; Oxidation-Reduction; zvířata; cévní endotel; vazodilatace; Nitric Oxide Synthase Type III; Cystathionine gamma-Lyase; signální transdukce; Endothelium, Vascular; Superoxides; Aorta, Thoracic; metabolický syndrom; hypertriglyceridemie; potkani Wistar; Superoxide Dismutase; Vasodilation; Male